Hepatitis B immunity in teenagers vaccinated as infants: an Italian 17‐year follow‐up study. (13th March 2014) - Spada, E.; Romanò, L.; Tosti, M. E.; Zuccaro, O.; Paladini, S.; Chironna, M.; Coppola, R. C.; Cuccia, M.; Mangione, R.; Marrone, F.; Negrone, F. S.; Parlato, A.; et al.
Abstract We assessed the persistence of hepatitis B surface antigen antibody (anti‐HBs) and immune memory in a cohort of 571 teenagers vaccinated against hepatitis B as infants, 17 years earlier. Vaccinees were followed‐up in 2003 and in 2010 (i.e. 10 years and 17 years after primary vaccination, respectively). When tested in 2003, 199 vaccinees (group A) had anti‐HBs <10 mIU/mL and were boosted, 372 (group B) were not boosted because they had anti‐HBs ≥10 mIU/mL (n = 344) or refused booster (n = 28) despite anti‐HBs <10 mIU/mL. In 2010, 72.9% (416/571) of participants had anti‐HBs ≥10 mIU/mL (67.3% in group A vs. 75.8% in group B; p 0.03). The geometric mean concentrations (GMCs) were similar in both groups. Between 2003 and 2010, anti‐HBs concentrations in previously boosted individuals markedly declined with GMC dropping from 486 to 27.7 mIU/mL (p <0.001). Fifteen vaccinees showed a marked increase of antibody, possibly due to natural booster. In 2010, 96 individuals (37 of group A and 59 of group B) with anti‐HBs <10 mIU/mL were boosted; all vaccinees of the former group and all but two of the latter had an anamnestic response. Post‐booster GMC was higher in group B (895.6 vs. 492.2 mIU/mL; p 0.039). This finding shows that the immune memory for HBsAg persists beyond the time at which anti‐HBs disappears, conferring long‐term protection.